STRATEGI PEMERINTAH DESA DALAM PENGEMBANGAN DESA WISATA CIPTA KARYA - Yoseph Erbito; Solikhin; Yesika Ola (Mount Hope Economic Global Journal, 2024)
The purpose of the study was to determine the strategy of the Cipta Karya Village government to successfully raise the tourism potential it has and the culture that is still preserved. The study used a qualitative method, with a qualitative descriptive approach, the type and source of data are primary data and secondary data. Based on the results of the study, it can be concluded that the strategy used in efforts to develop the Cipta Karya Tourism Village uses a strategy by utilizing the potential of natural tourism and artificial natural tourism, utilizing and creating facilities and infrastructure at tourist attractions, reading business opportunities in order to be able to open businesses for the community, so that the Cipta Karya Village Government has appeared to play an active role in supporting the development of the Cipta Karya Tourism Village by reading business opportunities from the potentials that arise from the activities of tourists and the community in the Tourism Village, so that the Cipta Karya Village Government plays an active role in supporting the development of the Cipta Karya Tourism Village.